Architectural accessibility of shools: Implications for individual education plans for pupils with physical disabilities - Nikolić Snežana (Specijalna Edukacija i Rehabilitacija, 2015)
In available studies of inclusive practice and IEP, emphasis was placed on the activities undertaken to reach the accessibility of teaching programs for students with special needs. Architectural accessibility of schools and its implementation for IEP has not been researched enough. The main aim of this research was to highlight the importance of architectural barriers for the process of creating IEP for pupils with physical disabilities, trough determining a current situation in regular elementary schools in Belgrade. An observation list, with 38 variables of architectural accessibility was used in this research. The sample consisted of 12 elementary schools in “Zvezdara” Municipality, Belgrade. The results show that there is complete architectural accessibility in nine out of 38 variables. All nine variables belong to “universal design”. In other variables, elements that measure specific components of architectural accessibility for pupils with physical disabilities mainly intermit. This must be taken into consideration when we discuss IEP, primarily from the aspect of planning additional help and support to professionals, providing additional time for pupils’ work and learning in class, and providing adequate place for learning.